1970
DOI: 10.1113/jphysiol.1970.sp009200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neurohypophysial hormones on fluid movement across isolated bladder of Rana cancrivora, Rana temporaria and Bufo melanostictus

Abstract: SUMMARY1. The rate of fluid movement across the wall of isolated amphibian urinary bladder was estimated using hemi-bladders of the tropical euryhaline Rana cancrivora, the temperate R. temporaria and the tropical Bufo melanostictdus.2. 6. The effect of extract of the pituitary gland of Rana cancrivora was examined on R. cancrivora bladder. It had a dose-response curve similar to the dose-response curve of vasotocin.7. The vasotocin content of the pituitary gland of R. cancrivora was estimated (a) from the dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Dicker & Elliott (1970 a, 6) examined the sensitivity of the skin and bladder of R. can¬ crivora, and found that in respect to water permeability the skin was not appreciably affected by neurohypophysial peptides, and that the urinary bladder was less responsive to these hormones than were bladders of freshwater amphibians. They also reported (Dicker & Elliott, 19706) that the neurohypophysis of R. cancrivora had less hormonal activity than neurohypophyses of freshwater amphibians. These findings indicate that the hypothalamopituitary response to dehydration may be less in R. cancrivora than in freshwater amphibians.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Dicker & Elliott (1970 a, 6) examined the sensitivity of the skin and bladder of R. can¬ crivora, and found that in respect to water permeability the skin was not appreciably affected by neurohypophysial peptides, and that the urinary bladder was less responsive to these hormones than were bladders of freshwater amphibians. They also reported (Dicker & Elliott, 19706) that the neurohypophysis of R. cancrivora had less hormonal activity than neurohypophyses of freshwater amphibians. These findings indicate that the hypothalamopituitary response to dehydration may be less in R. cancrivora than in freshwater amphibians.…”
Section: Introductionmentioning
confidence: 93%
“…Examination ofplasma and pituitary extracts for hydro-osmotic activity The effect of the diluted plasma or pituitary extract in altering the permeability of frog urinary bladder was measured by the method of Dicker & Elliott (19706) using the isolated urinary bladder of R. cancrivora (collected from fresh water). For each measurement a hemibladder was used, a solution consisting of 1 part Ringer and 4 parts water was placed inside it, and the bladder was suspended in aerated Ringer solution or Ringer plus a known amount of the plasma or pituitary extract being examined.…”
Section: Animalsmentioning
confidence: 99%
“…1967;Eggena el al., 1968], bladders of R. cancrivora were only slightly more sensitive to oxytocin than to vasopressin. No hydrosrnotic response was shown when either peptide was in concentrations smaller than 10 8 m [D icker and Elliott, 1970c]. The bladder of R. cancrivora was about 1,000 times more sensitive to vasotocin than to the mammalian peptides, but it was still markedly less sensitive than bladders of other anuran amphibians.…”
Section: Bladdermentioning
confidence: 99%
“…C h ew et al [1972] have investigated this problem quite recently. Using essentially the same method of isolated hemi-bladders described by D icker and Elliott [1970c], with Fig. 4.…”
Section: Bladdermentioning
confidence: 99%
See 1 more Smart Citation